Tax Inclusion Strategy: Transforming Voluntary Compliance through Educational Pathways - Abdullah, Syarif; Notonegoro, Hamdan Akbar; Hendra, Hendra; Septiana, Reski; Subekti, Subekti; Lestari, Rini Dwi; Yusuf, Maulana; Soegijono, Bambang; Taryana, Een; Imastuti, Imastuti (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2026)
Taxation is a vital instrument within a country's fiscal structure; however, low tax awareness remains a significant challenge in achieving voluntary compliance in Indonesia. This study aims to analyze the effectiveness of the tax awareness inclusion program as a long-term strategy to build tax-conscious citizenship through secondary education. Utilizing a participatory-educational communication approach, this initiative was conducted at SMPN 1 Cisata, Pandeglang, involving students as active subjects. Data were gathered through participant observation, interactive discussions, and post-socialization evaluations. The findings indicate that the use of adaptive visual media and message simplification effectively reduced negative stigmas and transformed students' understanding of tax roles as a social contract and a national development instrument. This study concludes that early internalization of taxation values not only enhances cognitive fiscal literacy but also positions students as potential agents of change in influencing public perception within their families. Strategic recommendations are directed towards systematic curricular integration to ensure the sustainability of a tax-aware culture in the future.